Establishment of an Exogenous Shocks Facility Under the Poverty Reduction and Growth Facility Trust. (Policy Papers; Policy Paper ;, 2005)
At the recent Board discussion on strengthening the Fund's assistance to low-income countries dealing with sudden and exogenous shocks, most Directors supported the establishment of an Exogenous Shocks Facility within the Poverty Reduction and Growth Facility Trust. In an earlier discussion, Directors noted that exogenous shocks could have significant negative impacts on developing countries' growth, macroeconomic stability, debt sustainability, and poverty, and that low-income countries are particularly vulnerable to shocks due to lack of diversification, limited capacity to build up reserves, and prohibitively expensive or unavailable market insurance. The international community can supplement national efforts for reducing vulnerability to shocks. Recent research shows that foreign assistance can be unusually effective in the aftermath of a shock. Such assistance needs to be available quickly, and it needs to be associated with sound adjustment policies and measures to reduce vulnerability to future shocks.